A cost-benefit analysis on the proposed Sibunag public market. - Mejia, Christian Theodore B.
The cost-benefit analysis on the proposed Sibunag public market was primarily undertaken to determine the economic as well as the financial feasibility of the project. To evaluate the proposed project the net present value (NPV), internal rate of return (IRR), benefit-cost ratio, and the profitability ratio was used. A 15 discount rate was used in this analysis following the standard discount rate applied on government infrastructure projects., For the purpose of analysis, primary and secondary data were obtained. Interviews and library work was conducted in order to gather adequate data for the analysis. The results obtained showed that the proposed project will increase the welfare of society. A sensitivity test was conducted to further evaluate the feasibility of the proposed project. The tests, results was slightly lower than the one applied with a 15 discount rate but nevertheless showed that the project was still feasible.